Task-oriented robotic rehabilitation for back mobility and functioning in a post-intensive care unit obese patient: A case report. - Lippi, Lorenzo; de Sire, Alessandro; Pizzorno, Marco; Turco, Alessio; Ariatti, Sarah; Curci, Claudio; Ammendolia, Antonio; Invernizzi, Marco (Journal of Back & Musculoskeletal Rehabilitation, 2025)
Background: Intensive care unit (ICU) acquired weakness is a detrimental condition characterized by muscle weakness, difficulty in weaning from mechanical ventilation, impaired mobility, and functional limitations, severely affecting overall quality of life. Obese patients face additional challenges due to obesity-related factors that exacerbate the negative effects of immobilization. Rehabilitation interventions have emerged as a crucial component of post-ICU care, but the rehabilitation management of obese patients remains challenging. Objective: to present the impact of implementing Walker View 3.0 SCX technology in post-intensive care unit rehabilitation of obese patient. Methods: A 69-year-old Caucasian man with a BMI of 44.8 kg/m2 was referred to the Cardiopulmonary Rehabilitation Unit at Alessandria Hospital, Italy, following an ICU admission for pneumonia. After a comprehensive multidisciplinary evaluation, the patient underwent an intensive rehabilitation program including physical exercises and a personalized dietary plan. A task-oriented robotic rehabilitation was added, utilizing the Walker View 3.0 SCX, for 30 min/day, 5 days/week. The robotic rehabilitation program focused on sit-to-stand mobility with weight support initially and progressed to a weight-supported robotic treadmill. Results: The patient showed clear improvements in physical function, muscle strength, and independence in activity of daily living (Barthel Index improved from 15 to 70, De Morton Mobility Index improved from 8 to 39, Medical Research Council Strength improved from 17 to 40, Functional Ambulation Classification score improved from 0 to 3, Handgrip Strength Test improved from 8.8 kg to 39.4 kg). Managed by a single physiotherapist, this approach showed positive results in enhancing functional outcomes, with potential benefits in reducing operator time and assistance costs. Conclusions: Integrating task-oriented robotic rehabilitation with Walker View 3.0 SCX showed promising outcomes for obese patients post-ICU. Personalized interventions with weight-bearing capabilities and real-time feedback optimized post-ICU care, enhancing functional outcomes, and potentially reducing operator time and assistance costs. Further research with larger samples is needed to validate the broader applicability and cost-effectiveness of robotic rehabilitation technologies in obese patients with ICU-acquired weakness.